Paano Nga Ba ang PETA Play (O Ano Nga Ba Ang Isang Play na Matatawag na PETAng-PETA) - Pambid, Manuel D. (Archīum Ateneo, 2024)
In telling the story of PETA, or the Philippine Educational Theater Association, this article reflects on the distinct characteristics that PETA plays have acquired in the more than 40 years it has served as the people’s theater—from the martial law years to the present, for the continuous expression of Filipino culture and heritage. The article shows the variety of PETA plays and the people behind their collaborative production, and ends with the present challenges of PETA as it reaches out to a younger generation of audience.